(untitled) (Architecture Image Studies, 2025)
This study examines the effectiveness of restorative justice in handling electoral crimes in Indonesia, with a focus on East Java. Elections are a cornerstone of democracy, requiring fairness, transparency, and integrity. However, elections often involve violations such as vote buying, voter intimidation, and ballot manipulation. Conventional legal approaches that emphasize punishment often fail to address the social roots of such offenses. Thus, restorative justice is proposed as a more humane and participatory alternative involving perpetrators, victims, and communities in the resolution process. This research’s methodology is that it applied the sociolegal methods, emphasizing the importance of recognizing legal unawareness among offenders. The key result of this research suggests that restorative justice has the potential to enhance electoral justice if it is implemented collaboratively among law enforcement, electoral oversight bodies, and civil society. Implementation challenges—such as limited public awareness and institutional support—are significant barriers that must be systematically addressed. The conclusion is that the effectiveness of restorative justice is influenced by a number of factors, including community understanding and awareness of the principles of restorative justice, support from the government and relevant institutions, and training for mediators and facilitators. The research purpose is that strengthening political education and interagency cooperation is essential to establish a fairer, more accountable electoral system in Indonesia. The scientific contribution from this research is that it provides the latest concept on the settlement of election crimes through restorative justice as part of criminal resolution in general elections.